Effect of temperature on the coherence time of a parabolic quantum dot qubit - Xiao*, Wei; Wang, Hong-Wei (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The effects of the temperature on the coherence time of a parabolic quantum dot (PQD) qubit are investigated by using the variational method of Pekar type. We obtain the ground and the first excited states’ eigenenergies and the corresponding eigenfunctions of an electron strongly coupled to bulk longitudinal optical phonons in the PQD. This two-level PQD system may be employed as a single qubit. The phonon spontaneous emission causes the decoherence of the qubit. We find that the coherence time will decrease with increasing temperature. It is an increasing function of the effective confinement length, whereas it is decreasing one of the polaron radius. We find that by changing the temperature, the effective confinement length and the polaron radius one can adjust the coherence time. Our research results would be useful for the design and implementation of the solid-state quantum computation.